High frequency optoelectronic oscillators based on the optical feedback of semiconductor mode-locked laser diodes - Haji, M.; Hou, L.; Kelly, A.; Akbar, J.; Marsh, J.; Arnold, J.; Ironside, Charlie (Optical Society of American (OSA), 2012)
Optical self seeding feedback techniques can be used to improve the noise characteristics of passively mode-locked laser diodes. External cavities such as fiber optic cables can increase the memory of the phase and subsequently improve the timing jitter. In this work, an improved optical feedback architecture is proposed using an optical fiber loop delay as a cavity extension of the mode-locked laser. We investigate the effect of the noise reduction as a function of the loop length and feedback power. The well known composite cavity technique is also implemented for suppressing supermode noise artifacts presented due to harmonic mode locking effects. Using this method, we achieve a record low radio frequency linewidth of 192 Hz for any high frequency (>1 GHz) passively mode-locked laser to date (to the best of the authors' knowledge), making it promising for the development of high frequency optoelectronic oscillators. © 2012 Optical Society of America.